Bio-Fertilizers via Co-Digestion: a Review - Abdulkarim, Abdulwadud Yusuf; Abdulsalam, Surajudeen; El-Nafaty, Usman Aliyu; Muhammad, Idris Misau (Traektorii͡a︡ nauki : mezhdunarodnyĭ ėlektronnyĭ nauchnyĭ zhurnal, 2019)
In diversifying the economies of most oil producing countries especially in regions with arable lands, Agriculture becomes the next choice aside mineral deposits. This has led to a search for an alternative to inorganic fertilizers, the alternatives are the biofertilizers. The paper discussed the classification of the anaerobic co-digestion process based on the application of inoculants to the biodigester feedstock to speed up the digestion process and the absence of inoculants. Biodigester feedstock also looked at the various mechanisms in the digestion process which includes hydrolysis, acidogenesis, acetogenesis, and methanogenesis, the pathways were illustrated with chemical equations and various microorganisms that take part in the anaerobic process were mentioned and tabulated. The types of biofertilizers, merits, and demerits, the difference between biofertilizers and organic fertilizers were comprehensively discussed. Current trends on the application of the co-digestion technique to improve the yield, nutrient, and safety of biofertilizers and also the recent progression on the technique were mentioned.